Vehicle Assistance Android Application - Muhammad Hafiz, Ramli; Mohd Arfian, Ismail (2016)
Technology is one of the most essential things to have for a person who lives in a modernization era. Hence, we developed the project called as Vehicle Assistance Android Application (V3A). The project was developed for the android user. This application was created to provide a convenience information [4] to the road user. As we all know, not everyone would save tow truck contact number in their phone, and even if they had saved [1][3], it might not be in their range of location